LAC MEL Specialists Use Peer Network to Improve Quality and Use of Evi dence - Anderson, Todd M; Prevatt, Amy (USAID, 2019)
Based on consultations and stocktakings with LAC Missions, the LAC Bur eau identified Mission Monitoring, Evaluation and Learning (MEL) Speci alists as influential decision makers regarding data and evidence use. The LAC Bureau aims to improve the quality and use of evidence for de cision making, and ultimately to improve development outcomes.